Importance of Lumbar Puncture in Late Onset Sepsis - Mariam Riaz, Sher Alam Khan, Alia Halim, Faisal Javed, Allah Nawaz Sultan (Pakistan Journal of Medical & Health Sciences, 2022)
Neonatal sepsis is the significant reason of neonatal mortality and morbidity and mostly results in extended hospitalization of infants in the neonatal intensive care unit. The sepsis was confirmed by a positive blood culture and a condition is considered clinical sepsis when the blood culture is negative. It is practically not possible to clinically differentiate sepsis from neonatal meningitis. However, a positive CSF for pathogenic bacteria indicates meningitis. Aim: The purpose of this study was to evaluate the frequency of late-onset sepsis in neonates with meningitis and to determine whether CSF analysis and lumbar puncture is mandatory in all cases of late-onset sepsis. Methods: This study was conducted in the Paediatrics department of CMH Abbottabad, and Sharif Medical City Hospital Lahore, and Pathology department of Women Medical and Dental College, Abbottabad for the duration from January 2022 to June 2022 among neonates with late neonatal sepsis. All neonates underwent clinical examination, history, routine tests (blood culture, C-reactive protein, complete blood count) and analysis and culture of cerebrospinal fluid for clinical evaluation of sepsis. Results: All 80 neonates tested positive for clinical sepsis: hematological sepsis was seen in 59 patients and 21 were CSF culture positive for sepsis; 8 (38.9%) of the 21 have positive CSF culture and 13 cases have negative blood culture. The most common clinical symptom was poor suction 70(87.5%), followed by weak moor 61(76.3%), and lethargy 46(57.5%). The Klebsiella spp was common organism seen in 15 children in the blood culture and the most communal organism in the cerebrospinal fluid culture was Staphylococcus aureus in 6 cases. Conclusions: The incidence of neonatal meningitis is high in new-borns with late-onset sepsis. Meningitis in neonates often transpires in the absence of bacteraemia. Therefore, the CSF examination and lumbar puncture are compulsory in all children with late onset sepsis. Keywords: Lumbar puncture, Meningitis, Neonatal sepsis